Optical Absorption Coefficient on-center donor impurity in a spherical core/shell quantum dots - M'zerd Safae; El Haouari M.; Feddi E.; Mora-Ramos M. E.; Jorio A.; Zorkani I. (MATEC Web of Conferences, 2020)
The polaronic effect on the linear, third-order nonlinear and total optical absorption coefficients have been calculated in the case of GaAs/AlAs core/shell quantum dot, with the impurity is positioned at the central radial position of the GaAs shell. The calculations are realized in the framework of the effective mass approximation and the numerical results are obtained by using a variational method and an infinite confining potential. The results show that the polaronic effect has a great influence on optical properties of core/ shell quantum dot, he causes a red-shift of the nonlinear optical coefficients associated to light absorption. Also, the polaronic effect is enhanced with the decreasing of quantum dot radius.